2016
DOI: 10.3329/bjp.v11i2.24933
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dual inhibitory activity of epifriedelanol isolated from <i>Cayratia trifolia</i> against ovarian cancer

Abstract: <p class="Abstract"><em>Cayratia trifolia</em> is used as diuretic, in tumors, neuralgia and splenopathy. However, compounds depicting anti-ovarian cancer activities from this plant source have not yet been identified and structurally characterized till date. In the present study, X-ray structure of epifriedelanol, a bioactive compound, isolated from the ethanolic extract of the <em>C. trifolia</em> and its binding affinities against a few proteins (HER2, EGFR and CXCR4) that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
(15 reference statements)
1
8
0
Order By: Relevance
“…It was performed in order to characterize the compounds on the basis of their ability to form favorable interactions within the active site of protein 16 The best active site (binding pocket/site) was determined based on the site score and hydrophobic/hydrophilic areas, which holds better binding cavity. 17 The binding site residues of CXCR4 were predicted and the results from this study showed that it may involve in the binding of substrate and small molecule. Thus, CXCR4 active site residues were picked to generate grid in the centroid of these residues for molecular docking approach.…”
Section: Adme Properties Predictionmentioning
confidence: 86%
“…It was performed in order to characterize the compounds on the basis of their ability to form favorable interactions within the active site of protein 16 The best active site (binding pocket/site) was determined based on the site score and hydrophobic/hydrophilic areas, which holds better binding cavity. 17 The binding site residues of CXCR4 were predicted and the results from this study showed that it may involve in the binding of substrate and small molecule. Thus, CXCR4 active site residues were picked to generate grid in the centroid of these residues for molecular docking approach.…”
Section: Adme Properties Predictionmentioning
confidence: 86%
“…Epi-friedelanol is present in several plants, such as in the root barks of Ulmus Davidiana [ 46 ], Cayratia trifolia [ 47 , 48 , 49 ], Vitis trifolia [ 50 ], Celtis sinensis [ 51 ], Mallotus apelta [ 52 ], and Ulmus pumila [ 53 ]. This triterpenoid has been reported to have anticancer [ 50 , 54 ], anti-inflammatory [ 51 ], and anti-senescence activity [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epi-friedelanol is present in several plants, such as in the root barks of Ulmus Davidiana [46], Cayratia trifolia [47][48][49], Vitis trifolia [50], Celtis sinensis [51], Mallotus apelta [52] and Ulmus pumila [53]. This triterpenoid has been reported to have anticancer [50,54], anti-inflammatory [51] and anti-senescence activity [46].…”
Section: Discussionmentioning
confidence: 99%